Endoplasmic reticulum stress is sufficient for the induction of IL-1β production via activation of the NF-κB and inflammasome pathways. Issue 8 (November 2014) - Kim, Sena; Joe, Yeonsoo; Jeong, Sun Oh; Zheng, Min; Back, Sung Hoon; Park, Sang Won; Ryter, Stefan W; Chung, Hun Taeg
The mechanisms underlying pathophysiological states such as metabolic syndrome and obesity include endoplasmic reticulum (ER) stress and aberrant inflammatory responses. ER stress results from the accumulation of misfolded proteins during stress conditions. However, the precise mechanisms by which ER stress modulates inflammation remain incompletely understood. In this study, we hypothesized that ER stress alone could represent a sufficient signal for the modulation of inflammasome-dependent cytokine responses. We found that several ER stress-inducing chemicals and the free fatty acid palmitate can trigger IL-1β secretion in various cell types, including monocytic leukemia cells, primary macrophages and differentiated adipocytes. We show that ER stress primes cells for the expression of pro-IL-1β via NF-κB activation and promotes IL-1β secretion. Enhanced IL-1β secretion depended on the activation of the NLRP3 inflammasome through a mechanism involving reactive oxygen species formation and activation of thioredoxin-interacting protein. Chemical chaperone treatment and the pharmacological application of carbon monoxide inhibited IL-1β secretion in response to ER stress. Our results provide a mechanistic link between ER stress and the regulation of inflammation, and suggest that modulation of ER stress may provide a therapeutic opportunity to block progression of low grade chronic inflammation to metabolic syndrome.